Hubungan Pendidikan, Pola Asuh Orang Tua dan Status Gizi dengan Perkembangan Bahasa Anak Usia Prasekolah di Paud Wilayah Pemulutan Selatan Tahun 2021 - Lopiyanah Lopiyanah; Helni Anggraini; Rizki Amalia (Universitas Batanghari Jambi, 2022)
Child development develops so rapidly. Early childhood is a child who is experiencing early childhood, namely those aged between 2 to 6 years whose emotional abilities will be grown so that after adulthood they are more likely to have intelligence. This study aims to determine the relationship between Education, Parenting Patterns and Nutritional Status in Children with Language Development of Preschool Age Children in PAUD South Pemulutan Region, Ogan Ilir Regency in 2021. The design of this study was an analytical survey using a cross sectional research design. The population in this study were all parents who had children attending PAud Sungai Lebung Ulu 24 people, Paud Sungai Lebung 49 people and Paud Naikan Bakarg (NTB) 29 people, totaling 102 people and the number of samples was 50 respondents. The sampling technique used is Proportional Random Sampling by lottery. Data analysis used chi square statistical test with a value of 0.05. The results of the chi square test showed that there was a significant relationship between education, p value = 0.035, parenting patterns, p value = 0.002 and nutritional status = 0.004 with the language development of preschool-aged children. Midwives are expected to increase knowledge to parents about the development of preschool age children to further increase stimulation of children, especially to improve their language development.